(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The improvement of the educational process in the study of pedagogical disciplines in the bachelor’s degree of a pedagogical university in the preparation of future teachers of humanitarian subjects reaches the predicted level with the result of professional and personal education - research on the theoretical and practical foundations of the use of innovative technologies in the training of future teachers - the educational process is being improved, better professional and personal training and education of future teachers of humanitarian subjects. The article reveals the roles of innovative pedagogical technologies used in the process of preparing future teachers (in the study of pedagogical disciplines), in improving the educational process, in improving the quality of teacher training, and in the professional and personal education of future specialists. And also, vocational and educational potentials of pedagogical disciplines and the possibilities of using innovative pedagogical technologies in the process of studying them were revealed.